2021
DOI: 10.1002/ejp.1825
|View full text |Cite
|
Sign up to set email alerts
|

Economic long‐term effects of intensive interdisciplinary pain treatment in paediatric patients with severe chronic pain: Analysis of claims data

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 43 publications
1
31
0
4
Order By: Relevance
“…Our study findings are also consistent with studies of intensive, inpatient-based interdisciplinary pain management programs, such as those evaluated in the studies by Evans et al, 7 Hechler et al, 8 Ruhe et al, 11 and Lopez Lumbi et al 13 These studies showed a decrease in overall health care utilization, which they examined through measures such as frequency of inpatient hospitalizations, pain-related ED visits, and specialist consultations, among other endpoint measurements examined over varying time periods. These studies also showed a reduction in health care costs as examined through measures such as subjective financial burden, health insurance claims, and cost estimate calculations using health care cost data tools.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study findings are also consistent with studies of intensive, inpatient-based interdisciplinary pain management programs, such as those evaluated in the studies by Evans et al, 7 Hechler et al, 8 Ruhe et al, 11 and Lopez Lumbi et al 13 These studies showed a decrease in overall health care utilization, which they examined through measures such as frequency of inpatient hospitalizations, pain-related ED visits, and specialist consultations, among other endpoint measurements examined over varying time periods. These studies also showed a reduction in health care costs as examined through measures such as subjective financial burden, health insurance claims, and cost estimate calculations using health care cost data tools.…”
Section: Discussionsupporting
confidence: 91%
“…Inpatient, intensive interdisciplinary pain treatment programs have also been associated with significant decreases in health care utilization and costs. 7 , 8 , 11 , 13 Evans et al noted an overall decrease in health care utilization but did not find a statistically significant reduction in ED usage, 7 whereas Ruhe et al found a decrease in health care utilization but no statistically significant difference in health care costs. 11 These studies included self-report questionnaires, semistructured interviews, physician remuneration and health insurance claims, among other measures used that may have associated biases.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…129 Few studies sought to evaluate the effects on sleep 80 and economic factors. 43,81 Although this article serves as a systematic review and meta-analysis, outcomes not attributable to a PedIMMPACT domain and single-study results are not included unless they are the only source of information for a given PedIMMPACT domain. Interested readers may refer to Supplement C (supplemental digital content, available at http://links.lww.com/PAIN/B607) and our OSF repository for single-study results and outcomes not attributable to PedIMMPACT domains (eg, pain coping and acceptance) with the caveat that these must be interpreted with utmost caution.…”
Section: Description Of Studiesmentioning
confidence: 99%